Cross-sensory experiences and the enlightenment: music synesthesia in context - Sola Chagas Lima, Eduardo (2019)
ABSTRACT: This study contemplates cross-sensory experiences as represented in late eighteenth-century thought, prior to George Sachs’s description of synesthesia in 1812. Sachs’s medical dissertation is now considered to be the first convincing scientific report of synesthesia in literature. Yet, less objective historical instances of cross-sensory experiences are not new to music, the visual arts, and poetry. Since these instances are difficult to assess on the part of modern disciplines (including musicology) due to their subjective nature, references to cross-sensory experiences prior to this date are either overlooked or simply ignored. The Medieval and Renaissance understandings of multisensory associations, deriving from natural science and cosmology, gradually gave way to rationalized discussions based on mathematics, physics, and practical experimentations as time elapsed. In eighteenth-century literature, allusions to sound-colour parallels enjoy special attention in the writings of Voltaire, Rousseau, Diderot, among others. In discussing the validity of these associations and their mechanisms, some authors extended these correspondences to other senses as well: touch, taste, and smell. This research is rooted in a historical survey of Enlightenment approaches to multisensory experiences—along with their priority for reason—discussing to which extent they are strictly ‘scientific,’ since the long eighteenth century still witnessed the coexistence of natural, cosmological, and philosophical readings of cross-sensory analogies. It also inquires whether Enlightenment thought established a philosophical foundation for initial investigations on music synesthesia. Finally, this study searches for a place for Sachs’s dissertation among Enlightenment debates—the philosophical and historical context that afforded its conception.